2020
DOI: 10.3390/nano10122541
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of an Ion-Imprinted Polymer for Aqueous Methylmercury Sorption

Abstract: Methylmercury (MeHg+) is a mercury species that is very toxic for humans, and its monitoring and sorption from environmental samples of water are a public health concern. In this work, a combination of theory and experiment was used to rationally synthesize an ion-imprinted polymer (IIP) with the aim of the extraction of MeHg+ from samples of water. Interactions among MeHg+ and possible reaction components in the pre-polymerization stage were studied by computational simulation using density functional theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The first cathodic peak, peak C1 at −0.48 V, represents the reduction in MeHg to methylmercury radical CH 3 Hg·, then, the second cathodic peak, peak C3 at −0.69 V, represents the reduction in CH 3 Hg· to Hg. It is worth noting that CH 3 Hg· can be disproportionate to (CH 3 Hg) 2 within a short time [ 14 ]; these reactions occur on the electrode surface during deposition. During the anodic scan, the stripping peak current correspondent to peak C1 is not observed; instead, one notices the presence of an anodic peak A2 at more positive potential, around 0.21 V, which indicates the oxidation of Hg to Hg 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first cathodic peak, peak C1 at −0.48 V, represents the reduction in MeHg to methylmercury radical CH 3 Hg·, then, the second cathodic peak, peak C3 at −0.69 V, represents the reduction in CH 3 Hg· to Hg. It is worth noting that CH 3 Hg· can be disproportionate to (CH 3 Hg) 2 within a short time [ 14 ]; these reactions occur on the electrode surface during deposition. During the anodic scan, the stripping peak current correspondent to peak C1 is not observed; instead, one notices the presence of an anodic peak A2 at more positive potential, around 0.21 V, which indicates the oxidation of Hg to Hg 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The present work reports the development and application of a highly selective and sensitive sensor for the quantification of MeHg. The sensor was developed using a carbon paste electrode modified with an imprinted polymer, which is highly selective toward MeHg (this was reported in our previous study [ 14 ]) and multi-walled carbon nanotubes-MWCNTs (which increase the charge transfer on the electrode surface). The electrochemical determination of MeHg was conducted by differential pulse stripping voltammetry (DPSV).…”
Section: Introductionmentioning
confidence: 99%
“…For rubidium recovery, Guerra et al [39] used organoclays for the immobilization of MBI. Recently, Mesa et al [40] reported the immobilization of 2-MBI onto ion-imprinted acrylic acid-based polymer and the removal of methylmercury. Different techniques were used for immobilizing 2-mercaptobenzimidazole on chitosan-based sorbents, including impregnation mediated by acetone [41], or chemical grafting [42].…”
Section: Introductionmentioning
confidence: 99%
“…Computational simulations or spectroscopic methods (e.g. UV-vis, FTIR or RMN) have already been used to preselect the best monomers candidates and template/monomer ratio for molecular or ion-imprinted polymers synthesis [39][40][41]. However, carrying out theoretical calculations and reliable modelings require specific knowledge.…”
Section: Introductionmentioning
confidence: 99%